(untitled) (BIRDEM Medical Journal, 2017)
Background: Complications of diabetes mellitus (DM) represent the major cause of morbidity and mortality in the modern era, diabetic polyneuropathy (DPN) being one of the most frequents. Nerve conduction study is employed to detect neuropathy. This study is done to see the electrophysiological pattern of diabetic polyneuropathy in a tertiary care setting. Methods: Study was carried out in 100 diagnosed DM patients attending department of neurology, BIRDEM General Hospital from July, 2015 to June, 2016. Diabetic patients with good glycaemic control were grouped in group A and that with poor glycaemic control in group B. Clinical questionnaire and neurological examination were administered, and nerve conduction study (NCS) were performed using standard techniques. Results: Among the 100 patients studied, 54 (54%) patients were Male and 46 (46%) patients were Female. 39% patients who had normal HbA1C was designated as group A and 61% patients having high HbA1c was designated as group B. Mean age of patients in group A was 55.02±10.45 years and group B was 54.94±11.13 years. Mean duration of diabetes in group A was 10.49±4.43 years and group B was 12.44±5.14years. Alterations in NCS included lowered amplitudes and slowed conduction velocities. Most common axonal pattern was found in peroneal nerves and most common demyelinating pattern was found in sural nerves. Sensory conduction velocity in significantly reduced in all sensory nerves in group B in comparison to group A. Compound motor action potential (CMAP) is significantly reduced on peroneal nerve in group B. Conclusion: Risk of neuronal involvement is increased as Diabetes mellitus progresses further which can be accelerated by poor glycaemic control. NCS is used to as an important tool to diagnose the peripheral neuropathy. Early diagnosis of neuropathy can be done by routine NCS and complications of neuropathy can be prevented by controlling Diabetes mellitus more meticulously. Birdem Med J 2017; 7(2): 114-120